1996
DOI: 10.1103/physrevlett.77.2049
|View full text |Cite
|
Sign up to set email alerts
|

New Hydrogen Distribution ina-Si:H: An NMR Study

Abstract: Hot-filament-assisted CVD deposited a-Si:H with low H concentration and low defect density has been examined by 1 H NMR. It is demonstrated for the first time that H microstructures can be altered significantly in device quality a-Si:H films. In the present films, large H clusters account for 90% of the 2-3 at. % H atoms, with the remaining H more dispersed, but still aggregated in a small volume fraction of the material. These results suggest that an ideal a-Si:H network with low defect density and high struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
71
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 12 publications
14
71
0
1
Order By: Relevance
“…A different activation energy for electron mobility points to different kinds of traps [88][89][90] or traps residing in slightly different-structured material. This last idea might be comparable with results on hydrogen in a-Si:H obtained with NMR on highly structured HW-CVD a-Si:H, for which a non-homogeneous distribution of hydrogen throughout the material was found [61]. Dangling bonds on void surfaces or within a compact Si network will result in other activation energies for the release of trapped electrons.…”
Section: Measurementssupporting
confidence: 71%
See 2 more Smart Citations
“…A different activation energy for electron mobility points to different kinds of traps [88][89][90] or traps residing in slightly different-structured material. This last idea might be comparable with results on hydrogen in a-Si:H obtained with NMR on highly structured HW-CVD a-Si:H, for which a non-homogeneous distribution of hydrogen throughout the material was found [61]. Dangling bonds on void surfaces or within a compact Si network will result in other activation energies for the release of trapped electrons.…”
Section: Measurementssupporting
confidence: 71%
“…Furthermore, it is interesting to note that a smaller hydrogen content does not mean that there are more defects in the material. The lower hydrogen content is a striking similarity with HW-CVD material [61]. Mahan et al [60] showed differences in opto-electronic properties compared with RF-PECVD and reported better structural order of the HW-CVD material.…”
Section: Measurementsmentioning
confidence: 84%
See 1 more Smart Citation
“…High temperature a-Si:H, deposited by the hot wire (HW) technique, has demonstrated very different structural and electronic properties, including a reduced Staebler-Wronski metastability, a different H NMR 'signature', improved structural ordering, and a dramatic reduction in film internal friction, which until now had been thought to be unachievable for an amorphous material [1][2][3][4]. The additional possibility of depositing such materials at high deposition rates [5] has only added to its attractiveness as a candidate for incorporation into a solar cell structure.…”
Section: Introductionmentioning
confidence: 99%
“…Dengan teknik baru ini, Lapisan tipis yang dihasilkan mempunyai kualitas yang relatif lebih baik akibat dekomposisi silan pada permukaan filamen panas [8,9]. Selain itu teknik ini melibatkan parameterparameter deposisi yang relatif sedikit sehingga mudah dikontrol.…”
unclassified